Sleep and circadian rhythm actigraphy measures, mood instability and impulsivity: A systematic review. (December 2021) - Gillett, George; Watson, Gareth; Saunders, Kate EA.; McGowan, Niall M.
Abstract: The normal spectrum trait measures of mood instability and impulsivity are implicated in and comprise core symptoms of several psychiatric disorders. A bidirectional relationship between these traits and sleep disturbance and circadian rhythm dysfunction has been hypothesised, although has not been systematically assessed using objective measures in naturalistic settings. We systematically reviewed the literature following PRISMA guidelines, according to a pre-registered protocol (PROSPERO: CRD 42018108213). Peer-reviewed quantitative studies assessing an association between actigraphic variables and any measure of mood instability or impulsivity in participants aged 12–65 years old were included. Studies were critically appraised using the AXIS tool. Twenty-three articles were retained for inclusion. There was significant heterogeneity in the selection and reporting of actigraphic variables and metrics of mood instability and impulsivity. We identified emerging evidence of a positive association between circadian rest-activity pattern disturbance and delayed sleep timing with both mood instability and impulsivity. Evidence for an association with sleep duration, sleep efficiency or sleep quality was inconsistent. Future research should focus on longitudinal intra-individual associations to establish the directionality between these measures and may lead to the development of chronotherapeutic interventions for a number of psychiatric disorders.